Onset of Action, Clinical Duration, and Recovery Index of Rocuronium: A Comparison with Atracurium - Atia A1*, Abired A2, Ashour A1 (AlQalam Journal of Medical and Applied Sciences, 2017)
Background: Neuromuscular blocking agent (NMB) is a very essential adjuvant to general anesthesia. Atracurium besylate (benzenesulfonate NMB) and rocuronium bromide (aminosteroidal NMB) are commonly used non-depolarizing muscle relaxants in Tripoli hospitals, Libya. This study aimed at evaluating onset of action, clinical duration, recovery time conditions, and any possible side effects of two neuromuscular blockers widely used in operation at Tripoli hospitals, Libya. Methods: A total of 112 patients underwent elective general or orthopedic surgery were randomly included in this study. All cases were assessed for the use of muscle relaxant (onset of action, clinical duration, spontaneous recovery, and any possible side effects). Brief information about the study, the subject information and the type of surgery was taken and recorded in specific form before starting the operation. Results: We demonstrated that the percentage use of atracurium in operation was 27.6% [Median dose 40.35mg] in compare to rocuronium 72.4% [Median dose 35.18mg]. The main onset of action of atracurium was found to be 68.75±11.2sec, in compare to rocuronium onset of action 64.40±8.6sec. Further, the main duration of action of rocuronium was 33.57±3 min, while in atracurium, the duration was 35.45±5 min. The recovery index was 11.3±2 min in atracurium group, while it was 9.2±1 min in rocuronium group. There were no side effects noticed with the use of both muscle relaxants during operation. Conclusion: Rocuronium has a rapid onset of action with shorter clinical duration compared with atracurium. Moreover, the recovery index was significantly shorter in rocuronium than atracurium, with no side effect have been reported in this study with the use of both agents.